2020
DOI: 10.1007/s11011-020-00614-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in expressions of genes involved in the regulation of cellular processes in mucopolysaccharidoses as assessed by fibroblast culture-based transcriptomic analyses

Abstract: Recent studies indicated that apart from lysosomal storage of glycosaminoglycans (GAGs), secondary and tertiary changes in cellular processes may significantly contribute to development of disorders and symptoms occurring in mucopolysaccharidoses (MPS), a group of lysosomal storage diseases in which neurodegeneration is specific for most types and subtypes. In this report, using transcriptomic data, we demonstrate that regulation of hundreds of genes coding for proteins involved in regulations of various cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…This may indicate that the pathogenesis of LSDs is not limited to the primary cause—accumulation of the storage material. Such a hypothesis can be corroborated by recently published results demonstrating dysregulation of expression of hundreds of genes, coding for proteins involved in various cellular processes, in fibroblasts derived from patients suffering from mucopolysaccharidoses [ 51 , 106 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Ferroptosis Disorders As a Mechanism For Pathogenesis Of mentioning
confidence: 62%
“…This may indicate that the pathogenesis of LSDs is not limited to the primary cause—accumulation of the storage material. Such a hypothesis can be corroborated by recently published results demonstrating dysregulation of expression of hundreds of genes, coding for proteins involved in various cellular processes, in fibroblasts derived from patients suffering from mucopolysaccharidoses [ 51 , 106 , 107 , 108 , 109 , 110 , 111 ].…”
Section: Ferroptosis Disorders As a Mechanism For Pathogenesis Of mentioning
confidence: 62%
“…32 Such global changes in levels of transcripts and proteins encoded by them result in dysmorphology and dysfunctions of different cellular organelles (like nucleus, mitochondria, endoplasmic reticulum, Golgi apparatus), 33 as well as abnormalities in various cellular processes. 34 Among them, apoptosis, 35 cell activation, 36 proteasomal degradation, 37 homeostasis of different ions (especially Ca 2+ , Fe 2+ and Zn 2+ ), 38 signal transduction, 39 and cell cycle, 40 are especially strongly affected. It was suggested that even behavioral disorders appearing in Sanfilippo disease and some other MPS types might be partially caused by disturbed regulation of expression of specific genes.…”
Section: Complexity Of Sanfilippo Disease Pathomechanismsmentioning
confidence: 99%
“…Severe neurodegeneration is a major obstacle in the development of an effective therapy for this disease, as it is challenging to find an efficient way to deliver potential drugs, especially large molecules, to the brain [6]. Moreover, recent studies have indicated that although HS storage is the major pathomechanism of the disease, secondary processes, including the dysregulated expression of hundreds of genes encoding proteins involved in the structures and functions of various cellular organelles, as well as different cellular processes (such as metabolic processes, cell communication, signal transduction, cell development, movement of subcellular components, and the cell cycle), may significantly influence the pathomechanisms of Sanfilippo disease, hindering the development of effective therapies [11][12][13][14]. Recent failures in the clinical improvements of MPS III patients participating in clinical trials with different kinds of therapies, such as gene therapy [15], enzyme replacement therapy [16,17], and substrate reduction therapy [18], have confirmed the great challenge to finding an effective therapy for Sanfilippo disease [19].…”
Section: Introductionmentioning
confidence: 99%